Method for detecting surface carbon content of hot-rolled organic coating plate

By wiping and sonicating the organic coating on the surface of the hot-rolled plate with degreased gauze, and using an infrared combustion carbon sulfur meter to detect the C content in the coating, the problem that the prior art cannot quickly and accurately evaluate the corrosion resistance of the hot-rolled coated plate is solved, and rapid quantitative analysis and corrosion resistance evaluation of the surface coating content of the hot-rolled coated plate is achieved.

CN119880839AActive Publication Date: 2025-04-25武汉钢铁有限公司 +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411494002.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-04-25
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing corrosion resistance testing methods cannot quickly and accurately evaluate the surface coating amount and corrosion resistance of hot-rolled coated plates, and require simulating a harsh service environment or testing over a long period of time, so it is impossible to effectively evaluate the corrosion resistance of newly produced samples.

Method used

The organic coating on the surface of the hot-rolled plate was wiped and extracted by wiping and extracting the organic coating film by sonication and drying at low temperatures. Then, the content of C in the coating was detected using an infrared combustion carbon sulfur meter and the carbon content within a unit area was calculated to evaluate corrosion resistance.

Benefits of technology

It realizes a rapid quantitative analysis of the surface coating content of hot-rolled coated boards, which can accurately judge the corrosion resistance of the product, is simple to operate and short to consume time, and is suitable for rapid testing at the production site.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for detecting the surface carbon content of a hot-rolled coated plate. The method comprises the following steps: wiping and extracting an organic coating on the surface of the hot-rolled plate by adopting absorbent gauze with an organic solvent; immersing in an organic solvent for ultrasonic treatment, then taking out the gauze, leaching and drying to obtain an organic coating film; sequentially adding a magnetic conductive agent, a combustion improver and a cosolvent into the heating container, and measuring a blank C content value under the condition that the organic coating film is not introduced; adding the obtained organic coating film into a heating container, sequentially adding a magnetic conductive agent, a combustion improver and a cosolvent, then putting the mixture into an infrared combustion carbon-sulfur instrument, and determining the content of C in the sample; and subtracting the blank value obtained in the step (4) from the obtained C content, and converting into the content in the unit area to finally obtain the carbon content of the coating surface in the unit area. According to the method, efficient separation of the surface coating of the hot-rolled plate and quantitative analysis of the C element in the surface coating of the hot-rolled coated plate can be achieved, and rapid evaluation of the corrosion resistance of the hot-rolled plate with the coating is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material detection, and in particular relates to a method for detecting carbon content on the surface of a hot-rolled organic coating plate. Background Art

[0002] Steel materials are widely used in the industrial and automotive industries due to their high machinability and low preparation cost, such as compressor crankshafts, guide rails and rollers. However, ordinary steel materials are prone to wear failure or corrosion failure on the surface of workpieces due to their poor wear resistance, relatively low hardness, or poor corrosion resistance, which seriously affects the service life. Attaching a layer of functional coating material to the surface of steel materials is the most effective protection method. Using surface coating technology to process and repair various parts can play a role in pre-protection and repairing old and waste, and can also extend the service life of equipment.

[0003] Coating hot steel plates can effectively prevent the diffusion of oxygen and metal ions, thereby achieving anti-oxidation and anti-decarburization of steel billet heat treatment, and achieving surface functional differentiation of hot-rolled high-strength steel. By coating the surface of hot-rolled plates, the corrosion resistance of the product can be greatly improved and the service life of the workpiece can be extended. Therefore, it is particularly important to be able to quickly and accurately evaluate the corrosion resistance of hot-rolled coated products. At present, the main methods for evaluating the corrosion resistance of products include outdoor hanging film method, salt spray test, and weekly immersion method; among them, the outdoor hanging film test method generally requires 1-4 years of hanging film, and the samples are retrieved from the base station year by year, and then the weight loss analysis is performed to obtain the corrosion rate of the samples, thereby evaluating the corrosion resistance of the samples; and the salt spray test mainly examines the difference in corrosion resistance of samples under simulated chloride ion conditions. This method simulates the environment in which chloride ions exist in the air. The service environment is relatively harsh and cannot truly reflect the corrosion resistance of the product itself; and the weekly immersion method mainly examines the difference in corrosion resistance of samples in simulated industrial atmospheric environments. Both the salt spray method and the weekly immersion method require cutting samples at the production site and bringing them back to the laboratory for analysis. They also need to simulate the corrosion resistance of samples under very harsh service conditions, or examine the corrosion resistance of samples over a long period of time (more than 2 years). They cannot effectively evaluate the corrosion resistance of samples that have just been produced. The salt spray method examines the corrosion resistance of samples under chloride ion conditions, and the weekly immersion method simulates the corrosion resistance of samples for at least 2 years. None of the above three methods can be used to quickly evaluate the amount of surface coating on the product and the quality of the product's corrosion resistance. It is urgent to develop a method suitable for the production site to detect the content of surface coating on hot-rolled plates. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for detecting the carbon content on the surface of a coated hot-rolled plate in view of the problems and shortcomings of the existing corrosion resistance testing methods, so as to realize a rapid evaluation of the corrosion resistance of the coated hot-rolled plate.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for detecting carbon content on the surface of a hot-rolled coated plate comprises the following steps:

[0007] 1) Use degreased gauze soaked with organic solvent to wipe and extract the organic coating on the surface of the hot-rolled plate;

[0008] 2) immersing the absorbent gauze from which the organic coating has been extracted into an organic solvent for ultrasonic treatment to separate the absorbent gauze from the organic coating, and then taking out the gauze;

[0009] 3) washing the remaining mixed solution obtained in step 2) with an organic solvent and drying the mixture to obtain an organic coating film;

[0010] 4) Add magnetic conductive agent, combustion aid and solvent to the heating container in sequence, and measure the blank C content value without introducing organic coating;

[0011] 5) adding the organic coating film obtained in step 3) into a heating container, adding a magnetic conductive agent, a combustion aid and a solvent thereto in sequence, and then placing the film into an infrared combustion carbon-sulfur instrument to measure the C content in the sample;

[0012] 6) Convert the obtained C content into the content per unit area, subtract the blank value obtained in 4), and finally obtain the carbon content per unit area of ​​the coated surface.

[0013] In the above solution, the thickness of the organic coating on the surface of the hot-rolled plate is less than 20 μm.

[0014] In the above scheme, the wiping extraction area of ​​the organic coating on the surface of the hot-rolled plate is >1600mm 2 .

[0015] In the above scheme, the organic solvent can be an alcohol solvent or a ketone solvent, etc.; specifically, one or more of ethanol, methanol, propanol, acetone, etc. can be selected.

[0016] In the above scheme, the power used in the ultrasonic treatment step of step 2) is 30-50W / L and the time is 10-15min.

[0017] In the above scheme, the magnetic conductive agent can be iron powder; the combustion aid can be tungsten particles or the like; the flux can be tin particles or the like.

[0018] In the above scheme, the temperature used in the drying step of step 3) is 30-40°C.

[0019] In the above solution, the heating container can be a ceramic crucible or the like.

[0020] Furthermore, in the step 4), the materials and their weight proportions include: 1.000-2.500 parts of magnetic conductive agent, 1.5000-3.000 parts of combustion aid, and 0.15-0.40 parts of tin particles.

[0021] In the above scheme, the present invention has no special restrictions on the type of organic coating on the surface of the hot-rolled plate, and the conventional organic coating systems in the steel field are all applicable to the detection method of the present invention.

[0022] The detection method of the present invention uses degreased gauze with an organic solvent to wipe the surface of the hot-rolled plate with an organic coating until the surface of the hot-rolled plate completely exposes the dark gray iron oxide surface, ensuring that the organic coating is completely extracted, and can achieve complete stripping of the surface coating of the hot-rolled plate, and there is no special requirement for the position and structural characteristics of the organic coating part to be tested and extracted, and it has wide applicability; then the degreased gauze and the organic coating are further separated, and finally the carbon dioxide infrared combustion method is used to detect the C content in the degreased gauze. When using this method, it is key to ensure that the C element is completely burned. Among them, since the organic coating sample itself is not conductive, it is necessary to add magnetic conductive materials and melting materials to help the sample burn completely to ensure the accuracy of the measured results. By detecting the difference in C content before and after the degreased gauze wipes the hot-rolled coated plate, the C content in the hot-rolled plate coating per unit area is calculated, thereby inferring the high or low content of the hot-rolled plate surface coating. The method can realize product surface positioning detection and analysis, is simple to operate, and takes a short time. It can more accurately obtain the C content in the hot-rolled plate surface coating, and provides an objective basis for judging the corrosion resistance of the hot-rolled plate.

[0023] The detection method of the present invention can basically realize the rapid judgment of the surface corrosion resistance of any part of the product surface, is simple to operate, and takes a short time. It can more accurately obtain the C content in the surface coating of the hot-rolled plate, and provide an objective basis for judging the corrosion resistance of the hot-rolled plate.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1) The present invention proposes for the first time to wipe the surface coating of the hot-rolled plate with degreased gauze (mechanical stripping, warm water immersion, hair dryer or detergent methods cannot effectively separate the coating), separate the coating film by ultrasound and low-temperature drying, and then use an infrared carbon-sulfur instrument to detect the C content in the sample, so as to achieve quantitative analysis of the C element in the surface coating of the hot-rolled coated plate;

[0026] 2) The detection method of the present invention can provide objective basis and detailed data for later determination of the corrosion resistance of hot-rolled coated plates, provide objective basis for screening whether products meet customer requirements, and provide strong technical support for product segmentation and providing different products for different needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1Samples 3# and 4# obtained in Example 2 were edge-sealed and placed in an outdoor exposure field. Photos of the samples were taken at 0, 2, and 4 weeks.

[0028] Figure 2 The standard curve drawn based on the C content and the C element intensity of the standard sample in Example 1;

[0029] Figure 3 Samples 1# and 2# obtained in Example 1 were edge-sealed and placed in an outdoor exposure field. Photos of the samples were taken at 0, 2, 4, and 6 weeks.

[0030] Figure 4 This is a standard curve drawn based on the C content and C element intensity of the standard sample in Example 2. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be fully and clearly described below in conjunction with embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0032] In the following examples, the hot-rolled plate with organic coating used is a hot-rolled plate with a conventional water-based epoxy resin coating on the surface, with an average thickness of 10 μm; the coating system is more tightly bonded to the substrate after being heated in hot water and is difficult to effectively wipe off.

[0033] In the following examples, the infrared carbon-sulfur instrument was preheated at 900° C. for about 30 min before testing; the tin particles were ultrasonically cleaned with acetone for 1-3 min, taken out and blown dry; and the ceramic crucible was preheated for 15 min and then set aside after heating.

[0034] Example 1

[0035] A method for detecting the carbon content on the surface of a hot-rolled plate with an organic coating comprises the following steps:

[0036] 1) Sample 1# is a coated hot-rolled plate, and sample 2# is an uncoated hot-rolled plate. The sample size is 50mm×50mm. Use degreased gauze soaked in anhydrous ethanol to wipe the organic coating on the surface of sample 1# and sample 2#, respectively, until the gray substrate is completely exposed on the surface of the sample. Weigh the mass of sample 1# and sample 2# before and after the organic coating is taken. The results are shown in Table 1.

[0037] 2) After the organic coating is wiped off, wipe the sample surface with absorbent gauze to see if there is black substance. Put the absorbent gauze into 30 mL of anhydrous ethanol and ultrasonicate for 5-10 minutes until the color of the absorbent gauze does not change, then take out the absorbent gauze;

[0038] 3) Rinse the degreased gauze with anhydrous ethanol for 3-5 times, pour all the solution into a watch glass, place the watch glass on an alcohol lamp to heat until all the solution evaporates, tap the edge of the watch glass with a clean brush, and pour the collected sample into a ceramic crucible;

[0039] 4) The infrared carbon-sulfur analyzer is preheated for about 30 minutes before testing. The tin particles are ultrasonically cleaned with acetone for 1-3 minutes, taken out and blown dry, and the ceramic crucible is preheated for 15 minutes. After heating, the collected samples are transferred to the ceramic crucible, and 1.000g of magnetic conductive agent (iron powder), about 0.2g of flux tin particles and 1.2000g of combustion aid are added to the ceramic crucible, and the blank C content value is measured without introducing the organic coating;

[0040] 5) Add 0.5000g of the standard sample C obtained in step 3) into a heating container, add 1.000g of magnetic conductive agent (iron powder), 1.5000g of combustion aid (tungsten particles) and 0.25g of flux (tin particles) thereto in sequence, and then put it into an infrared combustion carbon-sulfur instrument to determine the C content in the standard sample (the blank C content value can be automatically deducted after the instrument is set up), select standard samples to establish a working curve, and the C content ranges in the working curve are 0mg, 1mg, 5.3mg, 8.31mg, 11.31mg, and 30mg, respectively. The intensity of the C element of all standard samples is measured in the carbon-sulfur instrument, and a standard curve based on the C content and the C element intensity of the standard sample is drawn (see Figure 2 ), the relationship between intensity and concentration is y=-0.428+1.90x, R=0.9997; the sample collected in step 3) is placed in the carbon-sulfur analyzer in the same way to measure the intensity of the C element, and then the corresponding content of the C element in different samples is calculated based on the constructed standard curve.

[0041] Table 1 Carbon content on hot rolled plate surface

[0042]

[0043] From Table 1, we can see that the surface of sample 1# has an organic coating, while the surface of sample 2# has no organic coating. The C content in the coating of sample 1# is 7.5 g / m 2 .

[0044] The 1# and 2# samples were hung in an outdoor exposure area in Wuhan. Figure 3 In the same period of time, the area of ​​rust spots on the surface of sample 1# with organic coating is significantly smaller than that on the surface of sample 2# without organic coating. Starting from the 4th week, almost the entire surface of sample 2# was corroded. However, under the protection of organic coating, the degree of rust on the surface of sample 1# increased slightly from the 4th week to the 6th week, and the rust area was almost the same. The corrosion resistance of sample 1# is significantly better than that of sample 2#.

[0045] Example 2

[0046] A method for detecting the carbon content on the surface of a hot-rolled plate with an organic coating comprises the following steps:

[0047] 1) Provide two coated hot-rolled plates, sample 1# and sample 2#. Sample 1# uses coating A, and sample 2# uses coating B. The sample size is 80mm×40mm. Use degreased gauze soaked in anhydrous ethanol to wipe the organic coating on the surface of sample 1# and sample 2# respectively until the gray substrate is completely exposed on the surface of the sample. Weigh the mass of sample 1# and sample 2# before and after the organic coating is taken. The results are shown in Table 2.

[0048] 2) After the organic coating is wiped off, wipe the sample surface with absorbent gauze to see if there is black substance. Put the absorbent gauze into 30 mL of anhydrous ethanol and ultrasonicate for 5-10 minutes until the color of the absorbent gauze does not change, then take out the absorbent gauze;

[0049] 3) Rinse the degreased gauze with anhydrous ethanol for 3-5 times, pour all the solution into a watch glass, place the watch glass on an alcohol lamp to heat until all the solution evaporates, tap the edge of the watch glass with a clean brush, and pour the collected sample into a ceramic crucible;

[0050] 4) The infrared carbon-sulfur analyzer is preheated for about 30 minutes before testing. The tin particles are ultrasonically cleaned with acetone for 1-3 minutes, taken out and blown dry. The ceramic crucible is preheated for 15 minutes and set aside after heating. The collected samples are transferred to the ceramic crucible. About 1.000g of magnetic conductive agent (iron powder), 0.2g of flux tin particles and 1.2000g of combustion aid are added to the ceramic crucible. The blank C content value is measured without introducing organic coating;

[0051] 5) Add 0.5000g of the standard sample C obtained in step 3) into a heating container, add 1.000g of magnetic conductive agent (iron powder), 1.2000g of combustion aid (tungsten particles) and 0.2g of flux (tin particles) thereto in sequence, and then put it into an infrared combustion carbon-sulfur instrument to determine the C content in the standard sample (the blank C content value can be automatically deducted after the instrument is set up), select standard samples to establish a working curve, and the C content ranges in the working curve are 0, 1mg, 5mg, 7mg, 10mg, and 15mg, respectively. The intensity of the C element of all standard samples is measured in the carbon-sulfur instrument, and the working curve is drawn based on the standard curve of the C content and the C element intensity of the standard sample (see Figure 4 ); the sample collected in step 3) is placed in the carbon-sulfur instrument in the same way to measure the intensity of the C element, so as to calculate the corresponding content of the C element in different samples according to the constructed standard curve.

[0052] Table 2 Carbon content on hot rolled plate surface

[0053]

[0054] From Table 2, we know that the C content in the surface coating of sample 3# is 3.081 g / m 2 ; C content in the surface coating of sample 4# is 1.369g / m 2 By comparing the C element content per unit area, it can be seen that the corrosion resistance of sample 1# is better than that of sample 2#.

[0055] After sealing the edges of 3# and 4#, place them in an outdoor exposure field and take photos of the samples at 0, 2, and 4 weeks. The results are shown in the figure. Figure 1 ,like Figure 1 As shown in the figure, after the 1# sample was placed outdoors for 4 weeks, there was almost no obvious rust on the surface of the sample, while after the 2# sample was placed outdoors for the second week, obvious rust spots could be observed on the surface of the sample, and by the 4th week, the rust spots on the entire surface of the sample were very obvious. It can be seen that the corrosion resistance of the 1# sample is better than that of the 2# sample, which is consistent with the results of the measured C content in the coating.

[0056] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for detecting carbon content on the surface of a hot-rolled coated plate, characterized in that: The steps include: 1) Wipe and extract the organic coating on the surface of the hot-rolled plate with degreased gauze containing an organic solvent; 2) immersing the absorbent gauze from which the organic coating has been extracted into an organic solvent for ultrasonic treatment to separate the absorbent gauze from the organic coating, and then taking out the gauze; 3) washing the remaining mixed solution obtained in step 2) with an organic solvent and drying the mixture to obtain an organic coating film; 4) Add magnetic conductive agent, combustion aid and solvent to the heating container in sequence, and measure the blank C content value without introducing organic coating film; 5) placing the organic coating film obtained in step 3) in a heating container, adding a magnetic conductive agent, a combustion aid and a solvent thereto in sequence, and then placing the film in an infrared combustion carbon-sulfur instrument to measure the C content in the sample; 6) Subtract the blank value obtained in 4) from the obtained C content and convert it into the content per unit area to finally obtain the carbon content per unit area of ​​the coated surface.

2. The detection method according to claim 1, characterized in that: Wiping extraction area of ​​organic coating on hot rolled plate surface>1600mm 2 .

3. The detection method according to claim 1, characterized in that: The organic solvent is an alcohol solvent or a ketone solvent.

4. The detection method according to claim 1, characterized in that: Step 2) The power used in the ultrasonic treatment step is 30-50 W / L and the time is 10-15 min.

5. The detection method according to claim 1, characterized in that: Step 3) The temperature used in the drying step is 30-40°C.

6. The detection method according to claim 1, characterized in that: In the step 4), the materials and their weight proportions include: 1.000-2.500 parts of magnetic conductive agent, 1.5000-3.000 parts of combustion aid, and 0.15-0.40 parts of tin particles.

7. The detection method according to claim 1, characterized in that: The magnetic conductive agent is iron powder; the combustion aid can be tungsten particles; and the flux is tin particles.

8. The detection method according to claim 1, characterized in that: The thickness of the organic coating on the surface of the hot-rolled plate is less than 20 μm.

Citation Information

Patent Citations

  • Method for detecting surface residual oil quantity of rolled cold-rolling steel sheet

    CN102033002A

  • Method for removing silicon thick-film on silicon carbide substrate

    CN103204709A

  • Method for measuring content of residual carbon on surface of cold-rolled sheet

    CN111678912A

  • Method suitable for detecting carbon content and sulfur content in various alloys

    CN114088652A

  • Method for detecting residual iron on surface of cold-roll steel sheet

    CN115728292A